Methodological Approach to the Design of Digital Discourse Corpora in Spanish. Proposal of the CÓDICE Project - Vela Delfa, Cristina (2015)
Having analyzed the current situation of Spanish corpora—and the scarce representativeness of digital communication in them— and corpora from different types of interactions on digital platforms (e-mail, chats, SMSs), we noticed the need to create a repository of stable language samples aiming to solve this deficiency. Before implementing the CODICE, an open and collaborative repository of language samples from the digital discourse in Spanish, it becomes necessary to deal with the specific problems of compiling and transcribing this type of data. The present work addresses this approach aiming towards two goals: 1) establishing common standards, mainly concerning contextual and situational factors, in order to facilitate sociopragmatic analysis, and 2) developing ethical standards to ensure the anonymization of participants.